KEMELIMPAHAN JENIS COLLEMBOLA PADA HABITAT VERMIKOMPOSTING - Eladisa Ganjari, Leo (Widya Warta, 2012)
Collembola are small-sized animals that play a role in degradation of organic material.Vermicomposting is degradation process of organic material with earthworm as the main role players. The problem that arises is how the presence of Collembola is in vermicompostinghabitats. The purpose of this study was to determine the abundance and Collembola species that dominantly live in vermicomposting habitats. The study was conducted in December 2010 – August 2011 in Madiun. The reseach made use of rice straw, wood sawdust and chicken manure as the vermicomposting media. Compost sample was 27 cm3 (3 cm x 3 cm x 3 cm) in size, conducted in the first to fifth weeks. Deuteronomy was done 3 times. The result showed that Collembola abundance in the vermicomposting habitats of the fifth week (final) was 2 individuals per cm3. The dominant type of Collembola on the vermicomposting habitats was Pseudosinella sp.